Baby Ninth Amendments How Americans Embraced Unenumerated Rights and Why It Matters - Sanders, Anthony B (University of Michigan Press, 2023)
Listing every right that a constitution should protect is hard. American constitution drafters often list a few famous rights such as freedom of speech, protection against unreasonable searches and seizures, and free exercise of religion, plus a handful of others. However, we do not need to enumerate every liberty because there is another way to protect them: an ""etcetera clause."" It states that there are other rights beyond those specifically listed: ""The enumeration in the Constitution, of certain rights, shall not be construed to deny or disparage others retained by the people."" Yet scholars are divided on whether the Ninth Amendment itself actually does protect unenumerated rights, and the Supreme Court has almost entirely ignored it. Regardless of what the Ninth Amendment means, two-thirds of state constitutions have equivalent provisions, or ""Baby Ninth Amendments,"" worded similarly to the Ninth Amendment. This book is the story of how the ""Baby Ninths"" came to be and what they mean. Unlike the controversy surrounding the Ninth Amendment, the meaning of the Baby Ninths is straightforward: they protect individual rights that are not otherwise enumerated. They are an ""etcetera, etcetera"" at the end of a bill of rights. This book argues that state judges should do their duty and live up to their own constitutions to protect the rights ""retained by the people"" that these ""etcetera clauses"" are designed to guarantee. The fact that Americans have adopted these provisions so many times in so many states demonstrates that unenumerated rights are not only protected by state constitutions, but that they are popular. Unenumerated rights are not a weird exception to American constitutional law. They are at the center of it. We should start treating constitutions accordingly.